Optimal Placement Site and Angulation for Infrazygomatic Screw’s Insertion – A CBCT Study (Academia Journal of Medicine, 2024)
Anchorage control acts as foundation of the orthodontic  force system. Any undesirable movement of tooth should  be controlled otherwise existing malocclusion will worsen  and to prevail over this unwanted movement skeletal  anchorage has been introduced in orthodontic treatment.  Infrazygomatic screws are introduced to provide good  anchorage control. The study was conducted to determine  optimal site and angulation for placement of Infrazygomatic  screw. Study includes thirty patients (15 male and 15  female) above 18 years of age. IZC bone thickness and  height are measured using cone beam computed  tomographic images. Theia imaging software is used for  linear and angular measurement. One Way Analysis of  Variance (ANOVA) test was used to determine the relation  between bone thickness at different angle. Study concluded that with increase in insertion angle, infrazygomatic crest  bone thickness increases. The best site for mini screw  insertion in IZC is at angle of 70° in Durg population.
Keywords: Infra-zyomaticmini screw; Cone- beam computed Tomography; Skeletal anchorage